‘Caprice de chaconne’ (1671): Symmetry and proportions in Francesco Corbetta’s work for Baroque guitar - Rolfhamre, Robin (Early Modern Culture Online, 2018)
For performers of Early Music, there is an everlasting quest to unveil new perspectives on a historically distant repertoire in search of new ways of performing and understanding the music. This is true for all performers of Early Music, including Baroque guitarists. A currently very popular performance piece is Francesco Corbetta’s ‘Caprice de chaconne’ (1671, ff. 72–73), which is to be found in his 1671 Baroque guitar tablature-collection, La guitarre royalle. Displaying advanced technical performance skills, embroidered connections between temporal coordinates that border between fantasy and order, it serves as an excellent display, not only of the performer’s technical skills, but also of Corbetta’s virtuosity both as a performer and composer, and, as we will see, political participation. In this article I will suggest new perspectives that may provide an extended understanding of how Corbetta’s political wit and musical talent manifest themselves in his ‘Caprice de chaconne.’ By unveiling symmetrical and proportional aspects to this music, I will present a structure that might have an influence on the performance of the piece, situating it within the socio-political context of Louis XIV’s court and the cult of his Sun King persona.